518 DIVERTICULECTOMY WITH EXTENDED MIOTOMY FOR TREATMENT OF ESOPHAGEAL INTRATHORACIC DIVERTICULUM. (17th September 2021) - Bianchi, Edno Tales; Lopes, Leticia; Fernandes, Felipe; Seiti, Caio; Szachnowicz, Sergio; Sallum, Rubens; Cecconello, Ivan
Abstract:  : The treatment of thoracic esophageal diverticulum is based on removing the diverticulum and treating the possible cause that gave rise to it. We associate a myotomy below the area of the diverticulum to treat any difficulty in emptying and decrease the esophageal pressure that may have led to the diverticulum. Methods: We show a video how to manage the esophagel diverticulum. Results: We show a video how to manage the esophagel diverticulum. Conclusion: The diverticulectomy should be associated with an extended miotomy. Video: https://www.dropbox.com/s/c1m2r0ic4mw4cb5/Bianchi%20ET%20-%20diverticulectomy.mp4?dl=0 .